Increasing Understanding Of Reading Through Sustained Silent Reading (SSR) At The Second Grade Students Of English Department Of STKIP PGRI Bangkalan - Mohammad Arief Wahyudi (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah IX Sulawesi, 2019)
There are five skills in learning English, namely reading, speaking, listening and writing. The five skills are related to one another. This has been taught from elementary to high school so all students must understand it. In reading skills (Reading), students must understand a reading technique because without understanding they will not understand the contents of the reading or the information contained therein. This was experienced by students in the second semester, especially the English department who was in STKIP PGRI Bangkalan. In solving the problem above, the researcher aims to introduce the method used by the lecturer, the Sustained Silent Reading (SSR) Method. This method can help lecturers to invite students to find information and express ideas or ideas. This research method is quantitative in the experimental study where there is only one class of 30 students in one group pre-test and post-test. From these results it can be concluded that there is significant progress between the mean score 34 in the pre-test and the post-test score 73